miR-429 mediates tumor growth and metastasis in colorectal cancer - Han, Yantao (Am J Cancer Res, 2017)
Colorectal cancer (CRC), presenting the third most common malignancy worldwide. In recent years, the aberrantly upregulation or downregulation of miRNAs in CRC have been evidenced in a number of studies. In this study, our results showed that the expression of miR-429 was significantly higher in CRC tissue compared with adjacent non-tumor tissue. In addition, our findings showed that miR-429 level was significantly associated with clinicoplathological features and prognosis of patients with CRC. Moreover, our findings showed that miR-429 exerted oncogenic effect by directly targeting HOXA5, a transcription factor of HOX families that is involved in the development and progression of CRC.